Secretoneurin A regulates neurogenic and inflammatory transcriptional networks in goldfish (Carassius auratus) radial glia - Dillon F. Da Fonte; Christopher J. Martyniuk; Lei Xing; Adrian Pelin; Nicolas Corradi; Wei Hu; Vance L. Trudeau (Scientific Reports, 2017)
Abstract Radial glial cells (RGCs) are the most abundant macroglia in the teleost brain and have established roles in neurogenesis and neurosteroidogenesis; however, their transcriptome remains uncharacterized, which limits functional understanding of this important cell type. Using cultured goldfish RGCs, RNA sequencing and de novo transcriptome assembly were performed, generating the first reference transcriptome for fish RGCs with 17,620 unique genes identified. These data revealed that RGCs express a diverse repertoire of receptors and signaling molecules, suggesting that RGCs may respond to and synthesize an array of hormones, peptides, cytokines, and growth factors. Building upon neuroanatomical data and studies investigating direct neuronal regulation of RGC physiology, differential gene expression analysis was conducted to identify transcriptional networks that are responsive to the conserved secretogranin II-derived neuropeptide secretoneurin A (SNa). Pathway analysis of the transcriptome indicated that cellular processes related to the central nervous system (e.g., neurogenesis, synaptic plasticity, glial cell development) and immune functions (e.g., immune system activation, leukocyte function, macrophage response) were preferentially modulated by SNa. These data reveal an array of new functions that are proposed to be critical to neuronal-glial interactions through the mediator SNa.